1998
DOI: 10.1164/ajrccm.157.5.9708010
|View full text |Cite
|
Sign up to set email alerts
|

General Exercise Training Improves Ventilatory and Peripheral Muscle Strength and Endurance in Chronic Airflow Limitation

Abstract: We studied the impact of a 6-wk supervised, multimodality endurance exercise training program (EXT) on strength and endurance of ventilatory and peripheral muscles in patients with chronic airflow limitation (CAL), and determined whether potential improvements contributed to relief of exertional breathlessness (B) and perceived leg effort/discomfort (LE), respectively. Twenty breathless patients with stable CAL (FEV1 = 41 +/- 3% predicted; mean +/- SEM) were tested at 6-wk intervals at baseline, after a nonint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
3
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 32 publications
(41 reference statements)
14
102
3
11
Order By: Relevance
“…Although the between-group difference in the percentage increase in exercise time appears to be relatively large (104 vs. 68%), the substantial within-group variability precluded statistical significance. These increases in exercise duration are equivalent or greater than that previously reported in the COPD literature, as other investigators have reported improvements ranging from 43 to 77 percent [9][10][11] on CWR leg-cycle ergometer tests. Direct comparisons between studies are difficult, however, because the CWR exercise tests for the present study were performed at 85 percent of the subjects' VO 2peak achieved on the symptom limited progressive leg-cycle exercise test.…”
Section: Measurementssupporting
confidence: 68%
“…Although the between-group difference in the percentage increase in exercise time appears to be relatively large (104 vs. 68%), the substantial within-group variability precluded statistical significance. These increases in exercise duration are equivalent or greater than that previously reported in the COPD literature, as other investigators have reported improvements ranging from 43 to 77 percent [9][10][11] on CWR leg-cycle ergometer tests. Direct comparisons between studies are difficult, however, because the CWR exercise tests for the present study were performed at 85 percent of the subjects' VO 2peak achieved on the symptom limited progressive leg-cycle exercise test.…”
Section: Measurementssupporting
confidence: 68%
“…As described earlier, the potential advantage of measuring hL during CPET is that maximal effort is not required; the results of the studies that have used hL are again not unequivocal. In COPD patients, controlled studies did not observe changes in maximal fC or in maximal V9E [258,259,261].…”
Section: Symptom-limited Incremental Testmentioning
confidence: 84%
“…the improvement in V9O 2 ,peak after rehabilitation in COPD), particularly in patients with the most advanced disease. In some controlled studies, V9O 2 ,peak increased significantly [255][256][257][258], while other studies failed to observe a significant amelioration [259,260]. hL has also been used as an outcome variable, particularly in CHF patients.…”
Section: Symptom-limited Incremental Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that there is a reduction in symptoms such as fatigue and dyspnea after pulmonary rehabilitation programs 42,43 . In a study by Gigliotti et al 44 it was verified that training of the upper limbs, in a chronic manner, was able to reduce the symptom of dyspnea associated with increased inspiratory capacity and reduce the sensation of effort in the upper limbs.…”
Section: Discussionmentioning
confidence: 99%